“Everything Is Going To Be All Right”: Poetry as “Covid Comfort”? - Marion Naugrette-Fournier (Angles)
This article examines the artistic and, in particular, poetic response to the COVID-19 pandemic, that was witnessed in the Republic of Ireland in 2020. I will first try to show how this poetic response to the pandemic is linked to the historical and traditional role of the figure of the poet in Ireland, the “file”, and to the poet’s speaking out in the Irish public sphere during major historical events. With this in mind, I shall then analyze several case studies, such as the remarkable influence of a phrase uttered by Seamus Heaney used again during the Irish lockdown, or the impact of a poem by the President of the Republic of Ireland, Michael D. Higgins, himself a poet, eventually leading to the launch of an advertising campaign designed to reinforce physical distancing during lockdown. After examining other Irish artistic productions linked to Covid-19, I shall conclude with a counterexample, that is poet Paul Muldoon’s critical analysis of Derek Mahon’s famous poem, ‘Everything Is Going To Be All Right’, which enjoyed immense success during the pandemic in Ireland and was perceived by many as a poem of comfort and hope. But can any poem be reinterpreted as part of the literary sub-genre of “pandemic poetry”?